ANALYZING THE ANTECEDENTS OF CUSTOMER LOYALTY - Mohamed Badr ElDin Aboul-Ela, Ghadeer (British Journal of Marketing Studies, 2015)
This research study looked at analyzing the antecedents of customer loyalty namely; corporate image, customer satisfaction, and service quality. Based on the review of the previous literature, the research hypotheses were drawn. Questionnaires were designed and distributed to the tourists’ residents of the five stars hotels in Egypt. Findings revealed a positive relationship between corporate image and customer loyalty, customer satisfaction and customer loyalty and service quality and customer loyalty. It’s suggested that future research may be extended to other sectors and domains within Egypt.